PERFORMANCE OF ISPO-CERTIFIED INDEPENDENT SMALLHOLDER OIL PALM FARMING PRACTICES TOWARD SUSTAINABILITY IN PELEPAT ILIR DISTRICT, BUNGO REGENCY - Mirawati Yanita; Yusma Damayanti; Jamaluddin Jamaluddin; Gina Fauzia; Aris Munandar; Karina Rahmah; Muhammad Al Ghifari Rachmat Tanaka (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2025)
Oil palm plantations contribute to economic development in rural areas, the creation of employment opportunities, and the improvement of living standards. However, this commodity still suffers from sustainability problems. This is especially true among independent smallholders due to inadequate business scale to cover modern and sustainable agricultural practices with certification standards, especially those outlined in Indonesian Sustainable Palm Oil (ISPO).  The study aimed to provide an overview of ISPO-certified oil palm farming practices in Pelepat Ilir District, Bungo Regency.  The data were analyzed quantitatively and related to the farming practices of independent oil palm smallholders who are ISPO certified.  The results showed that farming ISPO-certified independent oil palm plantations were not per ISPO recommendations and norms, using fertilizers and herbicides was also not in line with recommendations, and ISPO-certified farmers received no FFB price differentiation.  In the future, it is hoped that independent oil palm farmers can adopt various sustainable farming practices recommended by ISPO standards. In addition, it is necessary to increase training and education from the government and relevant stakeholders on good agricultural practices.